Growth delay: an alternative measure of population health based on child height distributions. (17th February 2022) - Mansukoski, Liina; Qamar, Huma; Perumal, Nandita; Aimone, Ashley; Bassani, Diego G.; Roth, Daniel E.
Abstract: Background: Indicators of child height, such as mean height-for-age Z -scores (HAZ), height-for-age difference (HAD) and stunting prevalence, do not account for differences in population-average bone developmental stage. Aim: Propose a measure of child height that conveys the dependency of linear growth on stage rather than chronological age. Subjects and methods: Using Demographic and Health Surveys (2000–2018; 64 countries), we generated: (1) predicted HAZ at specific ages (HAZ regressed on age); (2) height-age (age at which mean height matches the WHO Growth Standards median); (3) Growth delay (GD), the difference between chronological age and height-age; (4) HAD; and (5) stunting prevalence. Metrics were compared based on secular trends within countries and age-related trajectories within surveys. Results: In the most recent surveys ( N  = 64), GDs ranged from 1.9 to 19.1 months at 60 months chronological age. Cross-sectionally, HAZ, HAD and GD were perfectly correlated, and showed similar secular trends. However, age-related trajectories differed across metrics. Accumulating GD with age demonstrated growth faltering as slower than expected growth for children of the same height-age. Resumption of growth at the median for height-age was rarely observed. Conclusion: GD is a population-level measure of child health that reflects the role of delayed skeletal development in linear growth faltering.